STUDENTSâ RESPONSE TOWARD THE DEVELOPMENT OF STUDENT WORKSHEET WITH PROBLEM BASED LEARNING IN COMPARISON MATERIAL AT CLASS VII-1 OF SMP NEGERI 1 KUANTAN MUDIK - Siregar, Syarifah Nur; Syofni, Syofni; Sukri, Metti; Solfitri, Titi (Vidya Karya, 2017)
Abstractâ This study aimed to determine students responses toward the development of student worksheet with problem based learning model in the comparison material. This study used 4-D model of development that consisted of four stages, namely the definition, design, development, and disseminate. Data collection instruments were sheets of validation and questionnaire of studentsâ responses. The questionnaire of studentsâ responses used Guttman scale consisting of 20 items of positive and negative statements. Grain statement was based on the aspects of accuracy, conformity with learning models, as well as the fulfillment of the terms of didactic, construction, and technical. Before tested to students, the student worksheet has been validated by three experts on mathematics education with very valid results (3.73). The student worksheet trial conducted to 32 students of class VII-1 SMPN 1 Kuantan Mudik, Kuantan Singingi, Riau Province during the second semester of the academic year 2016/2017. After carrying out learning by using worksheets, students were given the response questionnaire. Overall, students gave a positive response to the student worksheet which amounted to 94.37% categorized as very practical. Although the student worksheet already using Indonesian referring to Spelling Enhanced, there are some students who think that they find the unknown word or term on student worksheet. However, this is not a significant obstacle in learning because the student worksheet was developed for group learning so students can discuss things they did not understand with their group members. Â Keywords: problem based learning, studentsâ response, studentsâ worksheetÂ Abstrak. Penelitian ini bertujuan untuk mengetahui respon siswa terhadap Lembar Kerja Siswa berbasis Problem Based Learning yang dikembangkan. Pengembangan menggunakan model 4-DÂ yang terdiri dari 4 tahap yaitu Definition, Design, Development, dan Disseminate. Pengumpulan data menggunakan lembar validasi dan angket respon siswa.Â Angket respon siswa menggunakan skala Guttman yang terdiri atas 20 item berisi pernyataan positif dan negative. Item pernyataan didasarkan pada aspek akurasi, kesesuaian dengan model pembelajaran, serta pemenuhan syarat didaktik, konstruksi, dan teknis. Sebelum diuji kepada siswa, lembar kerja siswa divalidasi oleh tiga ahli pendidikan matematika dengan hasil yang sangat valid (3,73). Uji coba lembar kerja siswa dilakukan kepada 32 siswa kelas VII-1 SMPN 1 Kuantan Mudik, Kuantan Singingi, Provinsi Riau pada semester II tahun akademik 2016/2017. Setelah melakukan pembelajaran dengan menggunakan lembar kerja, siswa diberi angket respon. Secara keseluruhan, siswa memberikan respon positif terhadap lembar kerja siswa yang berjumlah 94,37% tergolong sangat praktis. Meskipun lembar kerja siswa sudah menggunakan bahasa Indonesia yang mengacu pada Ejaan yang Disempurnakan, ada beberapa siswa yang menemukan kata atau istilah yang tidak diketahui pada lembar kerja siswa. Namun, ini bukan masalah karena lembar kerja siswa dikembangkan untuk pembelajaran kelompok sehingga siswa dapat mendiskusikan hal-hal yang tidak mereka mengerti dengan anggota kelompok mereka.Â Keywords: problem based learning, studentsâ response, studentsâ worksheet